Anisotropic magnetoresistance and anomalous Hall effect in manganite thin films - Bibes, M; Laukhin, V; Valencia, S; Martínez, B; Fontcuberta, J; Gorbenko, O Yu; Kaul, A R; Martínez, J L (Journal of physics. Condensed matter, 2005)
We report on anisotropic magnetoresistance (AMR) and Hall effect measurements along the &[1bar 10]; and [001] directions in a (110)-oriented La2/3Ca1/3MnO3 thin film. While the electrical resistivity and the ordinary Hall coefficient are smaller for I along [001], evidencing some anisotropy of the Fermi surface, both the AMR and the anomalous Hall coefficient are larger when the current is applied along &[1bar 10];. Since these two phenomena originate from spin-orbit coupling effects, we state that our results support an anisotropy of the spin-orbit interaction in manganites. The possible origin of this anisotropy is discussed.